Group Assignment Management System (GAMS) / Muhammad Lokman Hakim Akram and Zurah Abu - Akram, Muhammad Lokman Hakim; Abu, Zurah (Faculty of Computer and Mathematical Sciences, 2023)
Each student must have experience in dealing with group assignments. Although there are many platforms available for students to use to organize group assignments nowadays such as WhatsApp, Microsoft Teams, Google Docs, and others, some students experience difficulties or problems while using them. Based on a survey conducted on students at an IPT in Malaysia, 100% of the respondents chose too many cluttered messages in a WhatsApp group as one of the issues faced in group work. 76% of the respondents became confused due to too many roles in multiple tasks and 64% chose overlooked assignment deadlines. Thus, this innovation introduced the development of a new system called the Group Assignment Management System (GAMS) for university students, which is a web-based system that assists a group of students in managing their group assignments. There are three users: administrator, leader, and member. This way, group partners can review and track different tasks performed individually online including assigning tasks, keeping track of teammates’ work progress, and getting SMS notifications regarding task datelines. Hence, it is hoped that this system will improve the management process from manual practice to an online system. Moreover, the SUS survey of GAMS scored 70.44 which means a good score was obtained and this system is acceptable to use.